PENYULUHAN DAN PELATIHAN PENGELOLAAN SAMPAH PLASTIK DALAM PENDEKATAN ZERO WASTE DI KELURAHAN TIWU GALIH - Sopia, Aniswatul; Ningsih, Diniah Insan Fitria; Susilawati, Eka; Fahad, Fahad; Wiguna, Made Arya; Humairah, Indah; Hafiz, Kamran; Nufus, Nurhayatun; Anggraini, Rina; Lestari, Titin (Jurnal Wicara, 2023)
Central Lombok Regency, the average waste production reaches 50 tons per day. The high production of waste requires counseling activities and waste management training. The purpose of waste management counseling and training is to help the community in understanding the correct procedures for sorting and managing waste with the 3R principle as the application of the zero waste concept so that the amount of waste heaps can be reduced. Counseling and training were held in Tiwu Galih Village, Praya District, Central Lombok at the end of June to early August. The methods applied in activities are approaches with residents, counseling, questions and answers and practices of using waste. Counseling and training in providing an understanding to the community about the correct procedures for sorting and managing waste so that the amount of waste can be reduced and the community is able to use inorganic waste into useful products and has economic value that can be used as a new business opportunity for the community, the concept of zero waste develops in the Tiwu Galih Village environment.